Super Encryption Feal Algorithm and Base64 Algorithm Image File Security - Br Bangun, Tiara; Achmad Fauzi; I Gusti Prahmana (Yayasan Kita Menulis, 2024)
In the rapidly advancing digital era, image file security has become a critical issue, especially with the increasing risks of data breaches and attacks on digital files. This study aims to enhance the security of image files by implementing a combination of two cryptographic algorithms: Fast Data Encipherment Algorithm- 4 (FEAL-4) and Base64. FEAL-4 is a symmetric encryption algorithm known for its high speed and processing efficiency, while Base64 is used for encoding binary data into ASCII format to ensure safer transmission. This research develops a super encryption system that integrates these two algorithms to protect the integrity and confidentiality of image files, particularly for BMP, JPEG, and PNG formats. The implementation was carried out using the Visual Basic programming language. The results of the study show that the combination of FEAL-4 and Base64 algorithms significantly enhances the security of image files, with a high success rate in the encryption and decryption processes.